2009
DOI: 10.4161/cib.2.6.9259
|View full text |Cite
|
Sign up to set email alerts
|

The expanding roles of caveolin proteins in microbial pathogenesis

Abstract: Caveolin proteins have been implicated in a wide range of cellular functions including lipid raft mediated endocytosis and regulation of cell signaling cascades. Recent discoveries have shown that these proteins are involved not only in regulating these homeostatic cellular functions, but also in the host response to a wide range of different infections. Both caveolin-1 and 2 have been shown to play important roles in pathogen uptake. While caveolin-1 is the most well studied member of this family, a growing b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 26 publications
0
25
0
Order By: Relevance
“…Membrane microdomains are essential for these endocytic processes. To disrupt these host cell domains prior to the infection with pneumococci, Calu-3 and MDCK-hpIgR cells were pretreated with increasing concentrations of methyl-␤-cyclodextrin (M␤CD), an oligosaccharide removing cholesterol from plasma membranes (Zaas et al, 2009), or nystatin, a sterol binding drug which disrupts lipid microdomains and impairs specifically caveolae-mediated endocytosis (Zaas et al, 2009). The presence of cholesterol chelators M␤CD or nystatin during 1 h of pneumococcal infection of host cells declined significantly the number of internalized pneumococci ( Fig.…”
Section: Pspc-pigr Mediated Pneumococci Uptake By Epithelial Cells Ismentioning
confidence: 99%
“…Membrane microdomains are essential for these endocytic processes. To disrupt these host cell domains prior to the infection with pneumococci, Calu-3 and MDCK-hpIgR cells were pretreated with increasing concentrations of methyl-␤-cyclodextrin (M␤CD), an oligosaccharide removing cholesterol from plasma membranes (Zaas et al, 2009), or nystatin, a sterol binding drug which disrupts lipid microdomains and impairs specifically caveolae-mediated endocytosis (Zaas et al, 2009). The presence of cholesterol chelators M␤CD or nystatin during 1 h of pneumococcal infection of host cells declined significantly the number of internalized pneumococci ( Fig.…”
Section: Pspc-pigr Mediated Pneumococci Uptake By Epithelial Cells Ismentioning
confidence: 99%
“…Lipid rafts are cholesterol and sphingolipid-rich microdomains of the plasma membrane [8], [9] which are exploited by many pathogens, including viruses, parasites and bacteria, to facilitate uptake of whole organisms and/or internalisation of toxins into host cells [10], [11], [12]. For example, Neisseria spec .…”
Section: Introductionmentioning
confidence: 99%
“…However, early studies suggested that caveolae may be an important alternative pathway for endocytosis of bacteria. 1,2,4,5 Chemical agents have been used to study the function of caveolae including nystatin, filipin and methyl-β-cyclodextrin (MβCD). These agents disrupt the cholesterol enriched lipid rafts.…”
Section: Bacteriamentioning
confidence: 99%